Exploring Adjustment Challenges of Nigerian International Graduate Students in American Higher Education (Comparative & International Education Series, 2022)
In this study, we focused on Nigerian international graduate and doctoral students studying at a research Historically Black College and University (HBCU) and  their lived experiences during their adjustment and transition to American higher education. Qualitative data were collected using an in-depth interview. The study findings informed higher education administrators and professionals about the adjustment challenges faced by Nigerian graduate students in their transition process and helped create awareness for adequate support services that can help improve in their transition.